The role of Nrf2 signaling pathway in diabetic cardiomyopathy: from pathogenesis to traditional Chinese medicine interventions - Gu, Huixian; Liu, Junchang; Jiang, Jie; Ma, Hongyan; Wu, Siyu; Sun, Longfei; Yao, Lan (Frontiers in Cardiovascular Medicine, 2025)
Diabetic cardiomyopathy (DCM), a common diabetic complication independent of hypertension, coronary heart disease and heart valve disease is a major cause of cardiovascular mortality. The pathogenesis of DCM is complex. The Nrf2-related signaling pathway which regulates oxidative stress, energy metabolism and mitochondrial physiology may play important role in the pathogenesis of DCM. Current treatments for DCM focus on blood glucose and pressure control, cardiovascular protection, lipid lowering and blockade of the renin-angiotensin system. However, the adverse drug reactions are inevitable. Traditional Chinese medicine (TCM) as a multi-target, multi-pathway treatment approach is considered to be a promising therapy for DCM. We reviewed how the Nrf2 and related signaling pathway regulated pathophysiological processes such as oxidative stress, inflammation, myocardial fibrosis, apoptosis, ferroptosis, autophagy and mitochondrial dysfunction in the progression of DCM and explored the potential mechanism and clinical value of TCM in DCM treatment. Based on a literature review, we found that various herbal compounds and combinations could alleviate DCM via the Nrf2 signaling pathway. This review highlighted the role of the Nrf2 signaling pathway in DCM progression and put forward new therapeutic strategies for DCM.